2014
DOI: 10.1152/ajpheart.00526.2014
|View full text |Cite
|
Sign up to set email alerts
|

Early life exposure to air pollution induces adult cardiac dysfunction

Abstract: Exposure to ambient air pollution contributes to the progression of cardiovascular disease, particularly in susceptible populations. The objective of the present study was to determine whether early life exposure to air pollution causes persistent cardiovascular consequences measured at adulthood. Pregnant FVB mice were exposed to filtered (FA) or concentrated ambient particulate matter (PM2.5) during gestation and nursing. Mice were exposed to PM2.5 at an average concentration of 51.69 μg/m3 from the Columbus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
50
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 49 publications
11
50
1
Order By: Relevance
“…However, at 14 days of age pups that were born to PM 2.5 exposed dams had significantly higher body weights compared to pups born to FA exposed dams. This observation is in agreement with our previous work where we demonstrated that mice exposed during the combined in utero and perinatal periods to PM 2.5 were born with LBW, but had significantly higher body weights at adulthood 9 . Similarly, it has also been shown that infants exposed to traffic-related pollution during early life gained postnatal weight despite reduced fetal growth 7 .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…However, at 14 days of age pups that were born to PM 2.5 exposed dams had significantly higher body weights compared to pups born to FA exposed dams. This observation is in agreement with our previous work where we demonstrated that mice exposed during the combined in utero and perinatal periods to PM 2.5 were born with LBW, but had significantly higher body weights at adulthood 9 . Similarly, it has also been shown that infants exposed to traffic-related pollution during early life gained postnatal weight despite reduced fetal growth 7 .…”
Section: Resultssupporting
confidence: 94%
“…An understanding of developmental plasticity provides a conceptual basis for these observations 8 . There is also substantial evidence suggesting a positive correlation between particulate air pollution exposure and adverse cardiovascular outcomes during the postnatal periods 9, 10 . In another study, cardiomyocytes cultured in media from PM-treated lung epithelial cells demonstrated contractile dysfunction 11 .…”
Section: Introductionmentioning
confidence: 99%
“…80 Air-pollution exposure during pregnancy is also associated with alterations in blood pressure 81 and birth weight, 80 as well as with the occurrence of preterm delivery, 82 and with future risk of CVD. 83 In conjunction with haemodynamic effects, inhaled particulate matter negatively affects vascular function. Minor increases in residential PM 2.5 levels have been associated with clinically relevant reductions in endothelial function (measured as a decrease from baseline in flow-mediated dilatation) among individuals in large US cohort studies.…”
Section: Blood Pressure and Vascular Functionmentioning
confidence: 99%
“…A similar exposure applied only throughout pregnancy affected only young adult male mice, exhibiting increased body weight, reduced blood pressure without change in basal cardiac function, and a higher susceptibility to heart failure than controls [99]. More recently, it was shown in mice that daily exposure during gestation and until weaning to ambient air particles at a concentration of 51.69 g/m 3 , 6 h/day, 7 days a week induced persistent cardiac dysfunction in the adult offspring [146].…”
Section: Cardiovascular Systemmentioning
confidence: 99%